Dimensi Metrik pada Graf Theta - Rahmadi, Deddy; Albar, Wakhid Fitri (Program Studi Matematika, Universitas Nusa Cendana, 2025)
Let G = (V, E) be a connected graph with vertex set V(G) and edge set E(G) . For any two vertices u and v in G , the shortest path distance between u and v is denoted by d(u, v). If W = {w_1, w_2, …, w_k} is an ordered set of vertices in the connected graph G , and v V(G), then the representation of vertex v with respect to W , denoted as r(v|W), is r(v|W) = (d(v, w_1), d(v, w_2), …, d(v, w_k)). If r(v|W) is distinct for each vertex v V(G), then W is referred to as a resolving set for G. The resolving set with the smallest cardinality is called the minimum resolving set, and the cardinality of this set is the metric dimension of G, denoted by (G). This paper explores the metric dimension of the theta graphs.